Multivalent interaction of cyclodextrin vesicles, carbohydrate guests, and lectins: A kinetic investigation - Vico, Raquel Viviana (2011)
An artificial glycocalix self-assembles when unilamellar bilayer vesicles of amphiphilic β-cyclodextrins are decorated with maltose-and lactose-adamantane conjugates by host-guest interactions. The maltose-decorated vesicles aggregate in the presence of lectin concanavalin A whereas the lactose-decorated vesicles aggregate in the presence of lectin peanut agglutinin. The kinetics of the orthogonal multivalent interfacial interactions present in this ternary system of vesicles, carbohydrates, and lectins were studied by time-dependent measurements of the optical density at 400 nm. The average vesicle and vesicle aggregate sizes were monitored by dynamic light scattering. The aggregation process was evaluated as a function of lectin concentration, vesicle concentration, and surface coverage of the vesicles by the carbohydrate-adamantane conjugates. The initial rate of vesicle aggregation scales linearly with the lectin as well as the cyclodextrin vesicle concentration. Furthermore, each lectin requires a characteristic critical density of carbohydrates at the vesicle surface. These observations allow a prediction of the response of the ternary supramolecular system at different concentrations of its components. Also, the effective binding site separation in a multivalent receptor such as a multiple binding site protein can be accurately determined. This methodology can be extended to multivalent noncovalent interactions in other ligand-receptor systems at interfaces. © 2010 American Chemical Society.